PENGARUH KUALITAS PELAYANAN DAN FASILITAS FISIK TERHADAP KEPUASAN PASIEN - Yuliantoharinugroho Yuliantoharinugroho; Mochamad Rofik; Wilis Fahlefi (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2023)
This study aims to analyze patient satisfaction at Rajawali Citra Hospital, Bantul. This study uses the variables of service quality and physical facilities as independent variables to analyze their effect on patient satisfaction as the dependent variable. Respondents in this study were patients who visited the Rajawali Citra Hospital, Bantul, with a sampling technique using this technique Random Sampling namely as many as 104 samples. The data analysis technique in this study used multiple linear regression analysis which was processed using the SPSS 17.0 program. The results showed that there was a positive and significant influence of service quality and physical facilities partially or simultaneously on patient satisfaction at Rajawali Citra Hospital, Bantul. Services that are fast, precise and supported by officers who are reliable in providing services and the ability to provide reliable explanations as well as physical facilities in hospitals that are complete, clean, well-maintained and safe can give satisfaction to patients. Keywords: Service Quality, Physical Facilities, Patient Satisfaction